Análisis de precios en la cadena de valor de la producción orgánica de hortalizas del grupo “Raíces” del centro experimental La Playita en el cantón La Maná, provincia de Cotopaxi, año 2012 - Millingalli Oña, Carla Yessenia (2015)
The present research analyzes the problem of the distribution of prices in the different activities of the value chain of the organic vegetables production group “Raíces” at the experimental center La Playita in La Maná canton, because at the moment farmers have not identified how much the cost of growing, harvesting, and selling this type of vegetables is with reference to the mentioned sector. In order to do this, the technique of value chain was used as a mechanism to determine prices of the organic vegetables production group “Raíces”.